PENGARUH ASET PAJAK TANGGUHAN, PERENCANAAN PAJAK DAN ARUS KAS BEBAS TERHADAP MANAJEMEN LABA: (Studi Empiris Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia) - Herni Diana Ambara; Wiwit Irawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to examine the effect of tax-deferred assets, tax planning and free cash flow on earnings management. The population in this study are companies in the property & real estate sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period. The method of determining the sample using a purposive sampling method, with several predetermined criteria, there are 8 companies with observations for 5 years, so that the total sample is 40 financial report data. The analytical method used is multiple linear regression analysis with the eviews 9 program. The results of the regression test in this study prove that deferred tax assets, tax planning and free cash flow simultaneously influence earnings management. Meanwhile, partially free cash flow has a negative effect on earnings management, while deferred tax assets and tax planning have no effect on earnings management.